Optimization of Inventory Inflation Budget Based on Spare-parts and Miscellaneous Costs of a Typical Automobile Industry (Journal of Engineering, 2023)
Brainstorming has been a common approach in many industries where the result is not always accurate, especially when procuring automobile spare parts. This approach was replaced with a scientific and optimized method that is highly reliable, hence the decision to optimize the inventory inflation budget based on spare parts and miscellaneous costs of the typical automobile industry. Some factors required to achieve this goal were investigated. Through this investigation, spare parts (consumables and non-consumables) were found to be mostly used in Innoson Vehicle Manufacturing (IVM), Nigeria but incorporated miscellaneous costs to augment the cost of spare parts. The inflation rate was considered first due to the market's price increase. Different types of vehicles were used to implement the Non-preemptive goal programming model and to predict the cost of procurement of the spare parts and miscellaneous and the profit for the current year. The result proved that the solution did not fully achieve the goals since the objective function is not equal to zero, but deviations for going below the profit goal and above the cost of procurement goal were significantly minimized.